Children's opera as a means of learning and unity in times of Covid-19: an interdisciplinary proposal for distance education - Gómez Núñez, María Isabel; Cano Muñoz, María Ángeles; Gómez Núñez, Juan Antonio (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2021)
Music education emerges as a teaching-learning process which contributes to students comprehensive development. The main objective of this work was to analyze the adaptation of the distance educational process in Musical Education, Spanish Language and Literature, Physical Education and Art Education areas in sixth grade of Primary Education, through an interdisciplinary proposal based on the The magic flute opera by WA Mozart. It is based on a mixed approach in which the results obtained through a case study are complemented with descriptive procedures of a quantitative cut. The data analysis showed positive results regarding the participation and satisfaction of the families, students and teachers. Similarly, students obtained optimal levels of content acquisition and key competences. The results of this work corroborate the importance of proposing interdisciplinary projects, as well as the possibilities provided by online teaching in Primary Education in isolation situations, such as those caused by Covid-19.
Keywords: Primary Education; Music education; distance education; interdisciplinarity; project based learning; opera